Cathepsin G Is Expressed by Acute Lymphoblastic Leukemia and Is a Potential Immunotherapeutic Target - Khan, Maliha; Carmona, Selena; Sukhumalchandra, Pariya; Roszik, Jason; Philips, Anne; Perakis, Alexander A.; Kerros, Celine; Zhang, Mao; Qiao, Na; John, Lisa S. St.; Zope, Madhushree; Goldberg, Jonathan; et al. (Frontiers in Immunology, 2018)
Cathepsin G (CG) is a myeloid azurophil granule protease that is highly expressed by acute myeloid leukemia (AML) blasts and leukemia stem cells. We previously identified CG1 (FLLPTGAEA), an HLA-A2-restricted nonameric peptide derived from CG, as an immunogenic target in AML. In this report, we aimed to assess the level of CG expression in acute lymphoid leukemia (ALL) and its potential as an immunotherapeutic target in ALL. Using RT-PCR and western blotting, we identified CG mRNA and protein, respectively, in ALL patient samples and cell lines. We also examined CG expression in a large cohort of 130 patients with ALL via reverse-phase protein array (RPPA). Our data show that CG is widely expressed by ALL and is a poor prognosticator. In addition to endogenous expression, we also provide evidence that CG can be taken up by ALL cells. Lastly, we demonstrate that patient ALL can be lysed by CG1-specific CTLs in vitro. Together, these data show high expression of CG by ALL and implicate CG as a target for immunotherapy in ALL.